Interactive on-line formative evaluation of student assignments - Dreher, Heinz (The Informing Science Institute, 2006)
Automated Essay Grading (AEG) technology has been maturing over the final decades of the last century to the point where it is now poised to permit a transition in ?assessment-thinking?. The administrative convenience of using objective testing to attempt to assess deep learning, learning at the conceptual level, has now been obviated by efficient and effective automated means to assess student learning. Further, the new generation AEG systems such as MarkIT deliver an unprecedented interactive formative assessment feedback capability, which is set to transform individualized learning and instruction as implemented in existing Learning Management Systems (LMS).